Exploring Party Loyalty and Electoral Behavior in Bangladesh’s Democracy (IUBAT Review, 2025)
Bangladesh is a democratic country where national and regional elections are organized for electing representatives. The question arises: are all the democratic process and practices going reasonable and smoothly? To find some answers, this study was conducted. The aim of this study is to explore the interplay between political loyalty, voter behavior, and democratic dynamics in Bangladesh, drawing  insights from a survey of 102 respondents, who took part from various regions and backgrounds (mainly from universities). Plus, it examines some unexplored or underexplored factors that influence voter decisions, such as party loyalty, ethnicity, financial incentives, and perceptions of transparency in governance. The findings reveal significant voter skepticism about the influence of money in politics, trust in political institutions. It also raises question to the effectiveness of democratic processes in Bangladesh. In addition, while community development and performance-oriented governance are emerging as voter priorities, some longstanding issues:  vote-buying, wealthy candidates' financial power despite having less political knowledge and party switching continue to challenge democratic consolidation in Bangladesh. It is quantitative method; 28 questions that were employed among the respondents, focusing on informed people. Finally, this paper suggested some policies: stricter campaign finance regulations, enhanced electoral integrity, and the promotion of performance-based politics, to improve democratic governance in Bangladesh.IUBAT Review—A Multidisciplinary Academic Journal, 8(1): 44-64